Applying the CHA2DS2-VASc score to predict the risk of future acute coronary syndrome in patients receiving catheter ablation for atrial fibrillation. (August 2020) - Chou, Ching-Yao; Chen, Yun-Yu; Lin, Yenn-Jiang; Chien, Kuo-Liong; Chang, Shih-Lin; Tuan, Ta-Chuan; Lo, Li-Wei; Chao, Tze-Fan; Hu, Yu-Feng; Chung, Fa-Po; Liao, Jo-Nan; Lin, Chin-Yu; et al.
Highlights: AF patients without catheter ablation have a higher risk of future ACS when compared to normal control group. The presence of AF without catheter ablation is an independent risk factor for future acute coronary events. Catheter ablation to AF could reduce future risk of acute coronary events over a very long-term follow-up. The cut-off value of baseline CHA2 DS2 -VASc score ≥ 4 can strongly predict future acute coronary events in patients with AF. Abstract: Objective: It remains unknown whether catheter ablation for atrial fibrillation (AF) reduces future acute coronary syndrome (ACS) risk or whether the CHA2 DS2 -VASc score has a role in predicting this risk. We aimed to compare very long-term risk of ACS between patients who received catheter ablation to AF or antiarrhythmic medications and controls without AF. Methods: Propensity scores were calculated for each patient and used to assemble a cohort of 787 patients undergoing AF ablation in 2003–2012. Patients were compared to an equal number of AF patients treated with antiarrhythmic medications and a control group without AF. Patients with previous coronary events were excluded. The primary endpoint was ACS occurrence. Results: Baseline clinical characteristics were comparable. After a mean 9.1 ± 3.2-year follow-up, the ablation group had lower incidence of new onset ACS than the medication and non-AF control groups (annual incidence: 0.15%. 0.78%, and 0.35%; with 2.67, 4.16, and 10.44 cases/1000 person-years, respectively; P < 0.001). After adjusting for multiple confounders, the ablation group had lower future ACS risk than the medication (hazard ratio [HR]: 0.20, 95% confidence interval [CI]: 0.13–0.30) and control groups (HR: 0.30, 95% CI: 0.20–0.45). The CHA2 DS2 -VASc score was a strong predictor of ACS (HR: 1.61, 95% CI: 1.47–1.76; AUC: 85.9%, 95% CI: 78.5–93.2%). A baseline CHA2 DS2 -VASc score ≥ 4 predicted future ACS (positive predictive rate: 14.3%). Conclusions: This study suggested that catheter ablation for AF may be beneficial to reduce future ACS risk in AF patients, and a high baseline CHA2 DS2 -VASc score can predict future acute coronary events.